Ziad Abu-Amr. Islamic Fundamentalism in the West Bank and Gaza. Muslim Brotherhood and Islamic Jihad. Bloomington: Indiana University Press, 1994. xvii, 169 pp. - Marín Guzmán, Roberto (Estudios de Asia y África, 1996)
-